Study on the relationship between hypertension and its comorbidities and dementia in community dwelling older adults in China - Qian-qian Nie; Gui-rong Cheng; Dan Song; Jing-yao Li; Lang Xu; Li-juan Zhang (Chinese General Practice Journal)
Background: China is experiencing an accelerated aging process, with an increasing number of elderly individuals suffering from chronic diseases. The association between hypertension, its comorbidities, and dementia in the elderly requires further investigation. Objective: To explore the prevalence of hypertension and its comorbidities in community dwelling older adults and their correlation with dementia, providing a reference for dementia prevention. Methods: This study utilized cross-sectional data from the 2018–2023 China Multicenter Dementia Survey (CMDS), which included demographic, chronic disease, and cognitive function assessments of 14,732 elderly individuals aged 65 and above. A multivariate logistic regression model was applied to analyze the correlation between hypertension, its comorbidities, and dementia. Results: Among the 14,732 elderly participants, 8,293 (56.3 %) had two or more comorbidities, and 7,786 (52.9 %) had hypertension with comorbidities. Of these, 2,569 (17.4 %) had one comorbidity, 2,064 (14.0 %) had two, 1,018 (6.9 %) had three, and 443 (3.0 %) had four. Dementia was present in 1,111 (7.5 %) participants. After adjusting for confounding factors, multivariate logistic regression revealed that the risk of dementia in individuals with hypertension was 1.516 times higher (95 % CI: 1.014–2.267) compared to those without hypertension. The risks of dementia for individuals with 1–4 comorbidities were 1.879 times (95 % CI: 1.312–2.692), 2.071 times (95 % CI: 1.428–3.004), 2.338 times (95 % CI: 1.612–3.392), and 2.591 times (95 % CI: 1.634–4.108), respectively. The highest risk (2.550 times, 95 % CI: 1.384–4.700) was observed in those with hypertension and cerebrovascular dementia. Stratified by gender and age, dementia risk increased significantly with the number of comorbidities, with statistical significance (P<0.05). The highest risks for males and females with hypertension and cerebrovascular dementia were 2.842 (95 % CI: 1.095–7.375) and 2.348 (95 % CI: 1.060–5.203), respectively. For individuals aged under 75 years, the highest risk was associated with hypertension and diabetes (OR=2.833, 95 % CI: 1.046–7.675), while for those aged 75 and above, hypertension combined with cerebrovascular disease showed the highest risk (OR=2.707, 95 % CI: 1.168–6.273). Among individuals with two comorbidities, hypertension with heart disease and cerebrovascular disease had the highest dementia prevalence (OR=3.559, 95 % CI: 1.338–9.468). In those with three comorbidities, hypertension combined with heart disease, cerebrovascular disease, and autonomic dysfunction had the highest dementia prevalence (OR=3.881, 95 % CI: 1.736–8.677). Conclusion: The prevalence of hypertension and its comorbidities is high among the elderly in China, and the risk of dementia is significantly increased in those with hypertension and its comorbidities. This risk shows variations based on age and gender.